Advances in Human Factors, Software, and Systems Engineering Proceedings of the AHFE 2017 International Conference on Human Factors, Software, and Systems Engineering, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book provides a platform for addressing human factors in software and systems engineering, both pushing the boundaries of current research and responding to new challenges, fostering new research ideas in the process. Topics include evolutionary and complex systems, human systems integration, smart grids and infrastructure, workforce training requirements, systems engineering education, and defense and aerospace. Based on the AHFE 2017 International Conference on Human Factors, Software, and Systems Engineering, held on July 17-21, 2017, Los Angeles, USA, this book is an inspiring guide for all researchers and professionals in the field of human factors, software and systems engineering.